Determinants of Buy Now, Pay Later (BNPL) Usage Among Generation Z - Nadhira Safa Ainunnisa; Erna Handayani; Bima Cinintya Pratama; Meydy Fauziridwan (JURNAL ECONOMINA, 2026)
The rapid expansion of digital financial services has transformed consumer payment behavior, particularly through the widespread adoption of Buy Now, Pay Later (Pay Later) services among Generation Z. Although Pay Later offers greater flexibility and convenience in digital transactions, its increasing utilization raises concerns regarding responsible financial decision-making. This study aims to examine the effects of Financial Literacy, Financial Self-Control, and Digital Financial Behavior on Pay Later Usage among Generation Z. A quantitative research approach was employed using a survey method involving 188 valid respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that Financial Literacy and Financial Self-Control do not have significant effects on Pay Later Usage. In contrast, Digital Financial Behavior has a positive and significant influence on Pay Later Usage, indicating that individuals who actively engage in digital financial activities are more likely to utilize Pay Later services. The structural model demonstrates substantial explanatory power, with an R² value of 0.793, indicating that the proposed model explains 79.3% of the variance in Pay Later Usage. These findings suggest that the adoption of Pay Later services among Generation Z is driven primarily by actual digital financial behavior rather than financial knowledge or self-regulatory capacity. This study contributes to the financial technology literature by emphasizing the importance of behavioral factors in explaining digital credit adoption and provides practical implications for policymakers, financial institutions, and fintech providers in promoting responsible digital financial behavior and sustainable Pay Later utilization.